How does light regulate chloroplast enzymes ? Structure–function studies of the ferredoxin/thioredoxin system - Dai, Shaodong; Schwendtmayer, Cristina; Johansson, Kenth; Ramaswamy, S; Schürmann, Peter; Eklund, Hans (My University, 2000)
A pre-requisite for life on earth is the conversion of solar energy into chemical energy by photosynthetic organisms. Plants and photosynthetic oxygenic microorganisms trap the energy from sunlight with their photosynthetic machinery and use it to produce reducing equivalents, NADPH, and ATP, both necessary for the reduction of carbon dioxide to carbohydrates, which are then further used in the cellular metabolism as building blocks and energy source. Thus, plants can satisfy their energy needs directly via the light reactions of photosynthesis during light periods. The situation is quite different in the dark, when these organisms must use normal catabolic processes like non-photosynthetic organisms to obtain the necessary energy by degrading carbohydrates, like starch, accumulated in the chloroplasts during daylight. The chloroplast stroma contains both assimilatory enzymes of the Calvin cycle and dissimilatory enzymes of the pentose phosphate cycle and glycolysis. This necessitates a strict, light-sensitive control that switches between assimilatory and dissimilatory pathways to avoid futile cycling (Buchanan, 1980, 1991; Buchanan et al. 1994; Jacquot et al. 1997; Schürmann & Buchanan, 2000).